2019
DOI: 10.1002/jcb.28752
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome activates AKT inducing cancer and metastasis

Abstract: Hyperactivated lysosome causes cancer and induces metastasis or cancer relapse. Such activation occurs during excessive, intense, and protracted oxidative burst in the lysosome. The burst induces the formation of the constitutively active (permanently active) AKT locus generating cancer complexity and robustness. Such condition has the tendency to persist by stabilized intense signaling inducing upregulation of cell function and metabolic setup at the higher level. Most intense activator of the lysosome is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 73 publications
(584 reference statements)
0
10
0
Order By: Relevance
“…Lysosome, an indispensable organelle, plays a crucial role in cell proliferation, strength, and apoptosis, which can digest large molecules as a membrane-encapsulated organelle in cells by degradative enzymes. Lysosome was discovered by De Duve in 1955, and the study revealed that they contain a variety of digestive enzymes which are called “hydrolase” that exhibit optimal activity in an acidic pH environment (pH = 4.5–6) within the lysosomal lumen. Therefore, lysosomes are the common degradation compartments of endocytosis and autophagy pathways, which could be considered the stomach of cell . In addition to the role of lysosomes in substrate degradation, recent findings also suggested that lysosomes play a leading role in cell signaling, cell migration, cholesterol homeostasis, and activation of apoptosis and tissue remodeling. Meanwhile, the dysfunction of lysosomes or abnormal lysosomal activity will lead to many diseases, such as neurodegenerative disease, Gaucher’s and Parkinson’s disease, lysosomal storage disease, progression of cancer, and inflammation. Therefore, studying the biological functions of lysosomes is essential for the survival and growth of organisms .…”
mentioning
confidence: 99%
“…Lysosome, an indispensable organelle, plays a crucial role in cell proliferation, strength, and apoptosis, which can digest large molecules as a membrane-encapsulated organelle in cells by degradative enzymes. Lysosome was discovered by De Duve in 1955, and the study revealed that they contain a variety of digestive enzymes which are called “hydrolase” that exhibit optimal activity in an acidic pH environment (pH = 4.5–6) within the lysosomal lumen. Therefore, lysosomes are the common degradation compartments of endocytosis and autophagy pathways, which could be considered the stomach of cell . In addition to the role of lysosomes in substrate degradation, recent findings also suggested that lysosomes play a leading role in cell signaling, cell migration, cholesterol homeostasis, and activation of apoptosis and tissue remodeling. Meanwhile, the dysfunction of lysosomes or abnormal lysosomal activity will lead to many diseases, such as neurodegenerative disease, Gaucher’s and Parkinson’s disease, lysosomal storage disease, progression of cancer, and inflammation. Therefore, studying the biological functions of lysosomes is essential for the survival and growth of organisms .…”
mentioning
confidence: 99%
“…To further reveal the function of NUE1 and its similar genes, functional enrichment analysis was performed and pathways involving lysosome, protein processing in endoplasmic reticulum, spliceosome, estrogen signaling pathway, hepatocellular carcinoma, dopaminergic synapse, and mTOR signaling pathway were found in the KEGG analysis. It is reported that hyperactivated lysosomes caused cancer and induced metastasis or tumor relapse (Radisavljevic, 2019), and tumor microenvironment could cause the redistribution of lysosomes toward the cell periphery, which enhanced invasion and metastasis by exocytosis of lysosomal hydrolases (Ballabio and Bonifacino, 2020). An experimental study demonstrated that NEU1 siRNA can significantly suppress proliferation, apoptosis, and invasion of tumor cells by targeting lysosomal membrane proteins (CLN3 and CLN5) (Ren et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt/mTOR is an important signal pathway in HCC carcinogenesis and plays a core role in promoting tumor cell proliferation (Xing et al, 2020). Moreover, hyperactivated lysosome causes permanent activation of AKT, which then controls lysosome and directly regulates cancer development and metastasis (Radisavljevic, 2019). Besides, the GO and PPI analyses demonstrated that NEU1 and its similar genes were involved in various biological processes and molecular functions, and some of them (e.g., autophagy, ncRNA metabolic process, and regulation of cell cycle process) were correlated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It could facilitate tumor cell migration and invasion via secreting acid hydrolase thereby increasing matrix remodeling ( 59 ). Lysosomes also promote cell adhesion and influence integrin secretion through attaching to ECM and regulating the dynamics of focal adhesions, activating AKT inducing cancer and metastasis ( 60 62 ). Taken together, the process is tanglesome, but has great therapeutic potential, such repression by the lidocaine, intervention by the stress of surgery.…”
Section: Mechanisms Of Cancer Metastasismentioning
confidence: 99%